Generic movement of eigenvalues for equivariant self-adjoint matrices - Dellnitz, Michael; Melbourne, Ian (Journal of Computational and Applied Mathematics)

Coherent Dynamics of Exciton Wavepackets in Semiconductor Heterostructures - Meier, Torsten; Koch, M.; Feldmann, J.; Göbel, E.O.; Jahnke, F.; Schäfer, W.; Thomas, P.; Koch, S.W.; Nickel, H.; Luttgen, S.; Stolz, W. (Proceedings der 8. International Winterschool on New Developments in Physics)
The coherent dynamics of exciton wavepackets in (GaIn)As/GaAs as well as (GaIn)As/Ga(PAs) multiple quantum well structures is studied by means of transient four-wave mixing (FWM) experiments. The wavepackets are generated by simultaneous excitation of several exciton transitions with laser pulses of about 100 fs duration. The time-integrated FWM signals exhibit a pronounced modulation superimposed on the overall decay which can be attributed to the quantum interference of the different eigenstates. In the time-resolved FWM signals this interference is not present, reflecting the interplay between many-body Coulomb effects and inhomogeneous broadening. This experimental technique is then employed to extract the exciton binding energies in pseudomorphic symmetrically strained (GaIn)As/GaIPAs) with various In contents.

Polarization selection rules for quantum beating between light and heavy holes in GaAs quantum wells - Meier, Torsten; Mayer, E.J.; Smith, G.O.; Kuhl, J.; Schulze, A.; Bennhardt, D.; Koch, S.W.; Thomas, P.; Hey, R.; Ploog, K. (Proceedings of the 5th European Quantum Electronics Conference)
Several recent experimental and theoretical studies have demonstrated the importance of exciton/exciton coupling due to Coulomb interactions for the nonlinear optical response of the 2D exciton in GaAs quantum wells (QWs).1,2 These results imply that multilevel models are required in order to provide a theoretically appropriate description of the nonlinear behavior. Previous application of a renormalized 9-level system has proven successful in describing the third-order response of hh-excitons in GaAs quantum wells.2 We present a comprehensive experimental and theoretical investigation of the polarization selection rules for degenerate- four-wave-mixing (DFWM) and quantum beating of hh and lh transitions in a GaAs QW. Depending on the polarization and temporal sequence of the three pulses simultaneous excitation of the hh and lh transitions generates either quantum beats (QB), no modulation of the signal, or a superposition of QB and polarization interference (PI) effects as proved by spectrally resolved (SR)-DFWM.

Die Artes liberales im frühen Mittelalter (5.-9. Jh.). Das Quadrivium und der Komputus als Indikatoren für Kontinuität und Erneuerung der exakten Wissenschaften zwischen Antike und Mittelalter - Englisch, Brigitte

Use of Symmetries in Tomography - Trächtler, Ansgar (Process Tomography - a Strategy for Industrial Exploitation)

Vollständige Modale Synthese stationär unstörbarer und stationär perfekter Zustandsregelungen - Trächtler, Ansgar (at-Automatisierungstechnik)

Static Behaviour of Drill Strings in Curved Boreholes - Sextro, Walter; Schmalhorst, B (Zeitschrift für angewandte Mathematik und Mechanik (ZAMM))

Modellbildung von Mehrwicklungstransformatoren bei quasi-stationären Feldstärkeverteilungen - Heinemann, Lothar

Theory for polarization-dependent four-wave-mixing signals in quantum wells - Meier, Torsten; Bennhardt, D.; Thomas, P.; Eccleston, R.; Mayer, E.; Kuhl, J. (Quantum Electronics and Laser Science Conference)
In degenerate four-wave-mixing (DFWM) experiments the polarization of the incident laser pulses can have a strong influence on the measured signal. For GaAs quantum wells a number of DFWM experiments were performed by using either parallel or perpendicular polarization of the incident laser pulses. Experimentally, it turned out that some characteristic features of the signal differ appreciably for the two configurations. In particular, different dephasing times, phase shifts of the quantum beats, different time-resolved behavior (echoes versus free-induction decay), and intensity dependence of the measured signal have been reported

Coherent coupling of exciton transitions in semiconductor quantum structures - Meier, Torsten; Koch, M.; Feldmann, J.; von Plessen, G.; Schulze, A.; Göbel, E.O.; Thomas, P.; Schmitt-Rink, S.; Shah, J.; Ploog, K.; Köhler, K. (Quantum Electronics and Laser Science Conference)
We investigate the coherent coupling of free and bound excitonic transitions, as wets as of distinct excitonic transitions arising from spatially separated quantum-well islands by means of time-resolved four-wave-mixing experiments.

Regelung der Querbewegung eines kamerageführten Straßenfahrzeugs - Trächtler, Ansgar; Lohmann, Boris; Struck, Günther (at-Automatisierungstechnik)

Analytische Berücksichtigung von Strukturbeschränkungen beim Reglerentwurf im Zustandsraum - Trächtler, Ansgar (VDI Nachrichten)

Entwurf von Ausgangsrückführungen mit der Vollständigen Modalen Synthese - Trächtler, Ansgar (at-Automatisierungstechnik)

Topologien und Schalterkonzepte für Schaltnetzteile hoher Leistung bei geringer Ausgangsspannung - Fröhleke, Norbert

Pulswechselrichtergespeiste Drehstromantriebe unter Berücksichtigung des Stromlückens - Wang, Yongfan

Georg von Reinbeck - Eke, Norbert Otto (Literatur Lexikon. Autoren und Werke deutscher Sprache. Bd. 9)

Die deutschsprachige Literatur Osteuropas und ihre Rezeption in der Bundesrepublik. Probleme und Chancen einer 'kleinen Literatur' - Eke, Norbert Otto (Deutsche Studien 29)
Auch erschienen in: Neue Zeitung [Budapest], Nr 28 vom 14.7.1990, S. 6-7, und Nr 29 vom 21.7.1990, S. 8-9, sowie Neue Literatur [Bukarest], H. 5-6/1990/91, S. 22-42

Zur Stabilität bei der Regelung von Systemen mit Durchgriff - Trächtler, Ansgar; Lohmann, Boris (at-Automatisierungstechnik)

Bifurcations in Dynamic Systems with Dry Friction - Stelter, Peter; Sextro, Walter (Bifurcation and Chaos: Analysis, Algorithms, Applications)
Dry friction is a main factor of self-sustained oscillations in dynamic systems. The mathematical modelling of dry friction forces result in strong nonlinear equations of motion. The bifurcation behaviour of a deterministic system has been investigated by the bifurcation theory. The stability of stationary solutions has been analyzed by the eigenvalues of the Jacobian. Period doublings and Hopf-bifurcations as well as turning points could be determined with the program package BIFPACK. Phase plane plots of periodic and chaotic motions have been shown for a better understanding of the bifurcation diagrams. Both, unstable branches and stable coexisting solutions have been calculated. Several jumping effects, which are typical for nonlinear systems, have been found.

Visualization in the Analysis Cycle of Observational Data, in Analyzing and Modeling Data and Knowledge - Domik, Gitta; Mickus, KD (Proceedings of the 15th Annual Conference of the "Gesellschaft für Klassifikation e.V." University of Salzburg)